Intergroup contact effects via ingroup distancing among majority and minority groups: moderation by social dominance orientation - Kauff, M; Schmid, K; Lolliot, S; Al Ramiah, A; Hewstone, M (Public Library of Science, 2016)
Five studies tested whether intergroup contact reduces negative outgroup attitudes through a process of ingroup distancing. Based on the deprovincialization hypothesis and Social Dominance Theory, we hypothesized that the indirect effect of cross-group friendship on outgroup attitudes via reduced ingroup identification is moderated by individuals' Social Dominance Orientation (SDO), and occurs only for members of high status majority groups. We tested these predictions in three different intergroup contexts, involving conflictual relations between social groups in Germany (Study 1; N = 150; longitudinal Study 2: N = 753), Northern Ireland (Study 3: N = 160; Study 4: N = 1,948), and England (Study 5; N = 594). Cross-group friendship was associated with reduced ingroup identification and the link between reduced ingroup identification and improved outgroup attitudes was moderated by SDO (the indirect effect of cross-group friendship on outgroup attitudes via reduced ingroup only occurred for individuals scoring high, but not low, in SDO). Although there was a consistent moderating effect of SDO in high-status majority groups (Studies 1-5), but not low-status minority groups (Studies 3, 4, and 5), the interaction by SDO was not reliably stronger in high- than low-status groups. Findings are discussed in terms of better understanding deprovincialization effects of contact.